PENISTAAN AGAMA DALAM PERSPEKTIF HUKUM POSITIF DAN ISLAM - Muannif Ridwan (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2016)
This study discusses the defamation of religion which became a hot topic amongIndonesian society today. As a lot of news about it in the print and electronicmedia. This issue drew public attention back, one of which stems from the releaseof video footage Tjahaja Basuki Purnama (Ahok) quoting Surah Al Maidah verse51. In the concept of the crime of blasphemy carries the consequences of an act oftarnishing religion. Policy formulation of the crime of defamation of religion showsthat the legal interest protected is religion itself. Defamation of religion have beendecided by the Constitutional Court as a criminal offense that is not contrary to the1945 Constitution, and therefore still workable and ensnare anyone suspected ofdoing so. In Islam, the Quran has a way to resolve cases of defamation of religionas in Surat an-Nisa verse 140 and surah Al-An'am verse 68.